2021
DOI: 10.1073/pnas.2116222119
|View full text |Cite
|
Sign up to set email alerts
|

RedChIP identifies noncoding RNAs associated with genomic sites occupied by Polycomb and CTCF proteins

Abstract: Nuclear noncoding RNAs (ncRNAs) are key regulators of gene expression and chromatin organization. The progress in studying nuclear ncRNAs depends on the ability to identify the genome-wide spectrum of contacts of ncRNAs with chromatin. To address this question, a panel of RNA–DNA proximity ligation techniques has been developed. However, neither of these techniques examines proteins involved in RNA–chromatin interactions. Here, we introduce RedChIP, a technique combining RNA–DNA proximity ligation and chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In addition, a higher proportion of the retained CBSs contain the previously defined U-motif, which increases CTCF-binding affinity. 34 CTCF binding can also be modulated by additional mechanisms such as those involving specific protein partners or long non-coding RNA; 46 , 47 nevertheless, we believe that the nature of the CTCF motifs and the presence of the U-motif are likely to be major determinants of the divergent activities of lost and retained CBSs. Indeed, combined assessment of CTCF motif numbers, CTCF consensus motif score, and the presence of the U motif could be used to successfully predict the presence of retained CBSs based on DNA sequence alone.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a higher proportion of the retained CBSs contain the previously defined U-motif, which increases CTCF-binding affinity. 34 CTCF binding can also be modulated by additional mechanisms such as those involving specific protein partners or long non-coding RNA; 46 , 47 nevertheless, we believe that the nature of the CTCF motifs and the presence of the U-motif are likely to be major determinants of the divergent activities of lost and retained CBSs. Indeed, combined assessment of CTCF motif numbers, CTCF consensus motif score, and the presence of the U motif could be used to successfully predict the presence of retained CBSs based on DNA sequence alone.…”
Section: Discussionmentioning
confidence: 96%
“…Using RNA antisense purification and RNA immunoprecipitation, we observed that in the presence of viral dsRNA, ARGI and CTCF interact with the regulatory regions of IFNβ and ISG15 , suggesting that viral infections in β cells promote ISG expression through the binding of ARGI and CTCF to regulatory regions of these antiviral genes. Recent studies have shown that CTCF can bind non-coding RNAs to modulate gene expression, including inflammation-related genes 54,55 . Using RedCHIP technique, a recent study identified several of cis- and trans-acting non-coding RNAs enriched at CTCF-binding sites in human cells, which may be involved in in CTCF-dependent chromatin looping and gene activation/repression 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CTCF can bind non-coding RNAs to modulate gene expression, including inflammation-related genes 54,55 . Using RedCHIP technique, a recent study identified several of cis- and trans-acting non-coding RNAs enriched at CTCF-binding sites in human cells, which may be involved in in CTCF-dependent chromatin looping and gene activation/repression 54 . Some studies have characterized the impact of CTCF and non-coding RNA interaction in the regulation of inflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches, RedChIP (combining an RNA–DNA proximity ligation technique Red-C [ 100 ] with ChIP) [ 95 ] and ChRD-PET (chromatin-associated RNA–DNA interactions, followed by paired-end-tag sequencing) [ 96 ], have been developed to enable the identification of specific ribonucleoprotein (RNP)-related RNA–DNA interactions by combining proximity-based ligation of RNA and DNA and chromatin IP ( Figure 2 b). RedChIP employs the ligation first, then follows with specific RNP ChIP.…”
Section: Approaches For Study Of Lncrna–protein Lncrna–dna and Lncrna...mentioning
confidence: 99%